2004
DOI: 10.1007/s00040-004-0771-z
|View full text |Cite
|
Sign up to set email alerts
|

Caste-specific gene expression in the stingless bee Melipona quadrifasciata ? Are there common patterns in highly eusocial bees?

Abstract: Caste polyphenism is a multifaceted phenomenon, most evident in the marked differences in reproductive capacity and longevity between queens and workers. The mechanisms underlying caste differentiation and division of labor are mainly addressed in the honey bee, and recently have been studied at the molecular level. Yet, generalizations drawn from studies on this model organism require validation by comparative studies. We choose Melipona quadrifasciata, a sister-group species to honey bees, to investigate dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…With respect to ESTs representing conserved sequences, the majority of the putative genes listed in Table 3 shows high similarity to sequences from honey bee workers, and the expression of some of these have already been reported for A. mellifera . For example, the transcripts previously identified in newly emerged Melipona workers as homologs of the Sin3A transcriptional regulator (Judice et al ., 2004), diacylglycerol kinase, RNA binding protein and Na + / K + ‐ATPase, have been described as overexpressed in foraging workers of A. mellifera (Tsuchimoto et al ., 2004). Genes such as dunce and one encoding a protein kinase C (PKC)‐like kinase were shown to be expressed in adult honey bee workers (Whitfield et al ., 2002), and their counterparts are involved in behavioural traits of Drosophila (Davis & Dauwalder, 1991; Tinette et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to ESTs representing conserved sequences, the majority of the putative genes listed in Table 3 shows high similarity to sequences from honey bee workers, and the expression of some of these have already been reported for A. mellifera . For example, the transcripts previously identified in newly emerged Melipona workers as homologs of the Sin3A transcriptional regulator (Judice et al ., 2004), diacylglycerol kinase, RNA binding protein and Na + / K + ‐ATPase, have been described as overexpressed in foraging workers of A. mellifera (Tsuchimoto et al ., 2004). Genes such as dunce and one encoding a protein kinase C (PKC)‐like kinase were shown to be expressed in adult honey bee workers (Whitfield et al ., 2002), and their counterparts are involved in behavioural traits of Drosophila (Davis & Dauwalder, 1991; Tinette et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we isolated two putative receptors that could also be related to nervous system functions: a guanylyl cyclase, which is the main receptor for nitric oxide in vertebrates and invertebrates (Bicker, 2001; Ott et al ., 2004), and a scavenger receptor, which interacts with a peptide binding domain named PDZ (Ikemoto et al ., 2000). Interestingly, two PDZ domain‐containing proteins were found in libraries generated as caste‐specific transcripts of M. quadrifasciata workers, one of them in the present work and the other one reported in a previous study (Judice et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one was a Differential Display Reverse Transcription (DDRT) PCR strategy (Judice et al, 2004) which permitted cloning and sequencing of 14 Expressed Sequence Tags (ESTs). These represent 12 genes that are overexpressed in newly emerged workers and two genes overexpressed in queens.…”
Section: From Caste To Blast: Differential Gene Expression In Meliponmentioning
confidence: 99%
“…In the present study we investigated transcript levels of ten genes previously identified as differentially expressed in the female castes of the stingless bee Melipona quadrifasciata (Judice et al , 2004, 2006), comparing their relative expression levels in diploid males to that of haploid ones, as well as to queens and workers. Real time RT-PCR assays were run on two time points in the adult life cycle, viz.…”
Section: Introductionmentioning
confidence: 99%